2022
DOI: 10.5713/ab.20.0621
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipid source and emulsifier on productive and physiological parameters of broilers

Abstract: Objective: This study aimed to evaluate the replacement of degummed soybean oil (DSO) by acid soybean oil (ASO) in diets with or without the inclusion of emulsifier on broiler performance, relative organ weight, lipase activity, intestinal morphometry, and nutrient digestibility.Methods: A total of 704 1-day-old male broiler chicks were allotted to a 2×2 completely randomized factorial design (with or without emulsifier × two lipid sources [ASO and DSO]), with eight replicates and 22 birds each. The metaboliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The morphological improvements could result from the synergistic effects of emulsifier interactions with the other feed ingredients as opposed to the influence of the emulsifier in isolation [ 27 ]. However, variations could also exist with no significant effects of emulsifiers on gut morphology being previously reported [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The morphological improvements could result from the synergistic effects of emulsifier interactions with the other feed ingredients as opposed to the influence of the emulsifier in isolation [ 27 ]. However, variations could also exist with no significant effects of emulsifiers on gut morphology being previously reported [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Cloft et al (2021) reported that the addition of lysolecithin led to the upregulation of carbonic anhydrase VII and interleukin 8-like 2, which have been also associated with better gut health (see Table 3). However, variations could also exist with no significant effects of emulsifiers on gut morphology being previously reported (Tenório et al, 2022;.…”
Section: Ileal Histomorphology and Gut Healthmentioning
confidence: 93%
“…Furthermore, Cloft et al (2021) reported that the addition of lysolecithin led to the upregulation of carbonic anhydrase VII and interleukin 8‐like 2, which have been also associated with better gut health (see Table 3). However, variations could also exist with no significant effects of emulsifiers on gut morphology being previously reported (Tenório et al, 2022; Wickramasuriya, Cho, et al, 2020). Concerning the vital role of the microbiota as an integral part of the gut health nexus alongside the diet, mucosa and immune system, further investigations on emulsifier effects on intestinal microbiota could be necessary.…”
Section: Application Of Exogenous Emulsifiersmentioning
confidence: 95%
See 1 more Smart Citation